2015
DOI: 10.1093/jrr/rrv006
|View full text |Cite
|
Sign up to set email alerts
|

The threshold of hypothyroidism after radiation therapy for head and neck cancer: a retrospective analysis of 116 cases

Abstract: The purpose of the present study was to determine the risk factors for developing thyroid disorders based on a dose–volume histograms (DVHs) analysis. Data from a total of 116 consecutive patients undergoing 3D conformal radiation therapy for head and neck cancers was retrospectively evaluated. Radiation therapy was performed between April 2007 and December 2010. There were 108 males and 8 females included in the study. The median follow-up term was 24 months (range, 1–62 months). The thyroid function was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 28 publications
8
43
0
1
Order By: Relevance
“…The present ROC curve analysis demonstrated that 5,160 cGy was a predictive threshold value, and the increased 3-year cumulative incidence of RIHT in the Dmean >5,160 cGy cohort confirmed this data (67.8% for Dmean >5,160 cGy and 44.6% for Dmean <5,160 cGy; P=0.036). Notably, the threshold value in the present study was >30 Gy reported by Fujiwara et al (29). Possible explanations are as follows: i) The dose in the target region was 54-60 Gy, and the prescribed dose was 59.4-66 Gy for PTV and 70-74.9 Gy for GTV boost, whereas the total dose in the Fujiwara et al (29) study was 60-66 Gy; and ii) The difference in the tumor types (NPC vs. head and neck malignancy types) and physicians may result in variations in the target area delineations.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The present ROC curve analysis demonstrated that 5,160 cGy was a predictive threshold value, and the increased 3-year cumulative incidence of RIHT in the Dmean >5,160 cGy cohort confirmed this data (67.8% for Dmean >5,160 cGy and 44.6% for Dmean <5,160 cGy; P=0.036). Notably, the threshold value in the present study was >30 Gy reported by Fujiwara et al (29). Possible explanations are as follows: i) The dose in the target region was 54-60 Gy, and the prescribed dose was 59.4-66 Gy for PTV and 70-74.9 Gy for GTV boost, whereas the total dose in the Fujiwara et al (29) study was 60-66 Gy; and ii) The difference in the tumor types (NPC vs. head and neck malignancy types) and physicians may result in variations in the target area delineations.…”
Section: Discussionsupporting
confidence: 49%
“…Notably, the threshold value in the present study was >30 Gy reported by Fujiwara et al (29). Possible explanations are as follows: i) The dose in the target region was 54-60 Gy, and the prescribed dose was 59.4-66 Gy for PTV and 70-74.9 Gy for GTV boost, whereas the total dose in the Fujiwara et al (29) study was 60-66 Gy; and ii) The difference in the tumor types (NPC vs. head and neck malignancy types) and physicians may result in variations in the target area delineations. In the present study, 30.6% (range, 1-88.2%) of thyroid tissues were exposed to radiation, resulting in the exposure of increased radiation doses to the thyroid gland.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We found that female gender and D mean were risk factors, as was found in previous studies. 8,9,13,14,25 The role of chemotherapy as a risk factor of RHT is unclear; 10,43,44 however, in our nomogram, chemo plays a significant role in RHT prediction (Figure 2, .70 points) because there was only 1 patient diagnosed with RHT who did not receive chemotherapy [(11.6%) 19 patients]. The study by Sachdev et al 23 identified V 50 as the only risk factor using a receiver-operating characteristic curve to obtain the cut-off point of V 50 for patients with RHT.…”
Section: Boomsma Et Almentioning
confidence: 99%
“…However, predictors and dose constraints varied according to the study. 13,14,[16][17][18][19][20][21][22][23][24][25] Nasopharyngeal carcinoma (NPC) is a prevalent cancer in southern China. Irradiation to the bilateral neck is a regular practice because of a high incidence 26 of neck node involvement.…”
Section: Introductionmentioning
confidence: 99%